Imágenes de la epidemia de fiebres tercianas en la Topografía hipocrática… (1795) de Félix Ibáñez - Płaczek-Kaszyńska, Katarzyna (Studia Romanica Posnaniensia, 2020)
The aim of the study is to analyse the images of the epidemic of tertian fevers in Topografía hipocrática o descripción de la epidemia de calenturas tercianas intermitentes malignas, continuo-remitentes, perniciosas complicadas (1795) by Félix Ibáñez (ca. 1738-1808), one of the most comprehensive studies dedicated to malaria in the 18th century Spain. They are examined from the perspective of the importance of visual representations of the illness in the 18th century, related to a radical transition from a logocentric to a visually dependent culture, which took place in the field of art and medicine in the Enlightenment.